Peran DPMPTSP Kota Banjar dalam Menarik dan Mengembangkan Penanaman Modal di Daerah - Nulhakim, Azhar Lukman; Arumi S, Isha’h Sekar; Hilda, Nurul; Maghfirotun, Siti Wahyu; Sudrajat, Bayu (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to analyze the role of the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Banjar City in attracting and developing regional investment. The research focuses on three key roles of DPMPTSP: administrative (regulatory), promotive (investment attraction), and facilitative (investment development). This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with key informants and documentation analysis from performance reports, investment realization data, and licensing policies. The findings reveal that the administrative role of DPMPTSP has been relatively efficient through the implementation of the Online Single Submission (OSS) system, yet coordination among related agencies (OPDs) and limited human resources remain significant challenges. In its promotive role, investment promotion activities tend to be passive and not yet based on the region’s specific sectoral potential. Meanwhile, the facilitative role, particularly aftercare services, is still reactive and lacks structured long-term investor support. The gap between policy expectations and field implementation indicates that DPMPTSP still functions more as an administrative body rather than a strategic driver of investment. Therefore, institutional restructuring and capacity building are required for DPMPTSP to transform into a proactive investment promoter and a key actor in sustainable regional economic development.